Analisis Penerapan Good Corporate Governance Pada Bank Syariah Indonesia Melalui Penerapan Pedoman Etika Bisnis Islam Dalam Bank Syariah Indonesia KCP Medan Tomang Elok - Nasution, Juliana; Setia, Dela; Subandi, Subandi; Fajar, Ramdanil (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
Financial institutions, especially banking, are experiencing rapid development and progress, Islamic banks as one of the sharia-based banks in Indonesia must make every effort to maintain their existence in the community.To maintain its existence, bank syariah KCP medan tomang elok implements Good Corporate Governance as a form of quality improvement and quality of resources and internal company. In its implementation, bank syariah Indonesia KCP medan tomang elok does not forget to remain based on Islamic Business Ethics. Islamic Business Ethics is one of the foundations to sustain the banking business sector. The purpose of this study is (1) to determine the application of Good Corporate Governance applied by Bank syariah Indonesia KCP medan tomang elok. (2) knowing the application of Islamic Business Ethics in Islamic bank KCP medan tomang elok. To obtain these data, researchers used documentation, observation and interviews as data collection methods.The Data obtained were then processed using qualitative descriptive analysis as a result of the study. Bank syariah Indonesia KCP medan tomang elok uses Islamic Business Ethics in implementing good corporate governance so as to avoid its business from internal company problems.